ผลการเปรียบเทียบความรู้ในวัฒนธรรมหลัก เรื่องอาหารภูเก็ต ของเด็กปฐมวัย: Comparative Results of Knowledge in Main Cultures About Phuket Food of Early Childhood - Noppawan Karo , นพวรรณ กาโร (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2022)
This study aimed at comparing levels of knowledge regarding major culture of early childhood through the management of the provision of learning experience model on Phuket food. The samples consisted of 30 early children aged between 5-6 who were studying in kindergarten year 2, the 2nd semester of academic year 2018, at PPAO Muang Phuket school. This school is under the supervision of the Phuket Provincial Administrative Organization. The research instruments were four lesson plans concerning Phuket food including: unit 1 Khanom Yi; unit 2 Khanom Ang Koo; unit 3 Khanom Ew Pueng; and unit 4 Khanom Ngor Siew, and tests to assess the level of knowledge on the major culture of early childhood. The data were analyzed with Mean (μ) and Standard Deviation (S.D.). The results were as follows. The results from comparing the levels of knowledge on the major culture of the early children revealed that, before studying with the provision of learning experience model, the mean score of the pre-test was 6.40 and the standard deviation was 2.11. However, after learning with the model, the mean score of the post-test became 17.13 and the standard deviation was 0.94. This showed that children’s knowledge of the main culture was improved.